2017
DOI: 10.1186/s12891-017-1864-y
|View full text |Cite
|
Sign up to set email alerts
|

The acutely injured acromioclavicular joint – which imaging modalities should be used for accurate diagnosis? A systematic review

Abstract: BackgroundThe management of acute acromioclavicular (AC) joint injuries depends on the degree of injury diagnosed by the Rockwood classification. Inadequate imaging and not selecting the most helpful imaging protocols can often lead to incorrect diagnosis of the injury. A consensus on a diagnostic imaging protocol for acute AC joint injuries does not currently exist. Therefore we conducted a systematic review of the literature considering three diagnostic parameters for patients with acromioclavicular (AC) joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 29 publications
0
65
0
Order By: Relevance
“…Weighted and nonweighted conventional images are used in clinical practice to assess vertical instability. 1,2,9 Patients who received a conventional radiological examination of both AC joints (weightbearing and nonweightbearing views) within high-grade AC joint separations (Rockwood III and V) were included in the present study. When all patients were analyzed, regardless of radiological imaging modality (weightbearing or nonweightbearing), an elevation of the clavicle was measured with increasing vertical dislocation, while no depression of the shoulder girdle could be observed.…”
Section: Discussionmentioning
confidence: 99%
“…Weighted and nonweighted conventional images are used in clinical practice to assess vertical instability. 1,2,9 Patients who received a conventional radiological examination of both AC joints (weightbearing and nonweightbearing views) within high-grade AC joint separations (Rockwood III and V) were included in the present study. When all patients were analyzed, regardless of radiological imaging modality (weightbearing or nonweightbearing), an elevation of the clavicle was measured with increasing vertical dislocation, while no depression of the shoulder girdle could be observed.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review showed high inter-and intra-observer reliability for diagnosing vertical instabilities of the clavicle using X-ray alone. Reliability for horizontal instabilities is much more variable [16].…”
Section: Discussionmentioning
confidence: 99%
“…Trauma to the AC joint and later stages of degenerative joint damage are primarily assessed on radiographic studies [ 15 , 82 ]. However, MRI can be helpful in evaluating earlier changes in AC joint degeneration, differentiating sprains and ligaments tears, and showing concomitant glenohumeral joint findings that may be present up to 18% of the time [ 83 , 84 ].…”
Section: Acromioclavicular Jointmentioning
confidence: 99%